Influence of the varnishing "surface" coverage on optical print characteristics - Hudika, Tomislav (Array, 2020)
Varnishing is often used to protect or decorate the print, but it can also influence the print’s colour appearance. Therefore, varnishing should enhance the print role, while colour change should be kept as low as possible. The aim of this paper is to evaluate inkjet UV LED varnishing by estimating optical print characteristics. Prepared offset prints were UV LED varnished in different surface coverage values (SCV) with a matte and gloss finish. The prints were evaluated by measuring gloss and colour coordinates. Secondly, varnishing was performed in a different SCV, which enabled assessing the optimal SCV, i.e. the most cost-efficient varnishing. The printing process was conducted in a standardized and controlled laboratory environment, regulated via the ISO 12647-2:2013 norm to ensure that the black colour was reproduced in the standard tolerance. The results showed that the colour difference is negligible (stays in the ISO tolerances), regardless of the varnishing SCV. On the other hand, the optimal printing gloss is at the SCV of 100%.